2018
DOI: 10.1002/1878-0261.12366
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel GLI1 target genes and regulatory circuits in human cancer cells

Abstract: Hedgehog (HH) signaling is involved in many physiological processes, and pathway deregulation can result in a wide range of malignancies. Glioma‐associated oncogene 1 (GLI1) is a transcription factor and a terminal effector of the HH cascade. Despite its crucial role in tumorigenesis, our understanding of the GLI1 cellular targets is quite limited. In this study, we identified multiple new GLI1 target genes using a combination of different genomic surveys and then subjected them to in‐depth validation in human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 49 publications
(64 reference statements)
2
22
0
Order By: Relevance
“…recently published that both GLI1 and FOXS1 are highly expressed and positively correlated with GLI1 in medulloblastoma samples 15 , further suggesting that the existence of FOXS1/GLI1 interplay in human cancers may not be dependent on the type of human tumor. Interestingly, FOXS1 expression can reduce GLI1 transcriptional activity, and GLI1/FOXS1 exhibit direct protein–protein interaction in HEK293A cells 15,37 . In our study, we found that GLI1 inhibited FOXS1 expression by binding the promoter regions of FOXS1, suggesting that GLI1 and FOXS1, two oncogenes, may combine and suppress each other’s expression.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…recently published that both GLI1 and FOXS1 are highly expressed and positively correlated with GLI1 in medulloblastoma samples 15 , further suggesting that the existence of FOXS1/GLI1 interplay in human cancers may not be dependent on the type of human tumor. Interestingly, FOXS1 expression can reduce GLI1 transcriptional activity, and GLI1/FOXS1 exhibit direct protein–protein interaction in HEK293A cells 15,37 . In our study, we found that GLI1 inhibited FOXS1 expression by binding the promoter regions of FOXS1, suggesting that GLI1 and FOXS1, two oncogenes, may combine and suppress each other’s expression.…”
Section: Discussionmentioning
confidence: 94%
“…Yumei Diao et al . recently reported that FOXS1 was one of the top targets of the GLI1 gene and was shown to act in a negative feedback loop limiting the cellular effects of GLI1 in medulloblastoma and rhabdomyosarcoma cells 15 . However, the interplay of GLI1 and FOXS1 in GC cells has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…GLI1 has a transcriptional activator function with a well‐established role in the Hedgehog signaling pathway, for which deregulation has been implicated in the pathogenesis of numerous malignancies 18 . GLI1 rearrangements have been identified in several malignant soft tissue tumors including pericytoma‐like tumors, 19,20 gastric plexiform fibromyxoma, 21 gastroblastoma, 22 and a group of malignant epithelioid neoplasms with frequent S100 protein expression.…”
Section: Discussionmentioning
confidence: 99%
“…It's well-known that Hedgehog (HH) signaling pathway plays critical roles in amount of cancers, including NB ( 43 46 ). GLI1, a terminal effectors of the HH factors, was reported to serve as an oncogene in wide ranges of cancers, such as breast cancer ( 47 ), CRC ( 48 ), prostate cancer ( 49 ), glioma ( 50 ), pancreatic cancer ( 51 ), gastric cancer ( 52 ), and cervical cancer ( 53 ).…”
Section: Discussionmentioning
confidence: 99%